A new fossil species of Euroleptochromus Jałoszyński (Coleoptera: Staphylinidae: Scydmaeninae) from Eocene Baltic amber - Yin, Zi-Wei; Cai, Chen-Yang (Zootaxa, 2018)
A new species of the extinct scydmaenine genus Euroleptochromus Jałoszyński (Mastigitae: Leptochromini), E. tuberculatus Yin & Cai, sp. nov., is described from Eocene Baltic amber. It can be separated from the two previously known congeners by the different proportions of the body parts and spination of the profemur, and more importantly, lack of an elongate postgenal process of the head. Our finding demonstrates for the first time a notable variability of the postgenal structures within Euroleptochromus.